Eco-Economic Incentives of Rational Land Use and Protection in Ukraine - SANNIKOV, Dmytro V. (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018, 2019)
The work represents a problem, which is defined by complex decision. The work shows that land recultivation and protection are usually offered as accompanying expenses for land exploitation. The authors demonstrate that the solution to the problem should be of eco-economic character. It is suggested to use not only legislative measures to enforce land users to restore land fund, but also to stimulate it. The work determines economic, legal and administrative solutions, which are aimed to enable the state to stimulate the principles or rational use of Ukrainian land resources. The work states that necessary measures have already been represented in Ukraine on the legislative level. It is suggested to be more oriented towards environmental constituent and to determine the direction of the formation of integrated perception of the state incentives mechanism. The novelty of study lies in the statement that incentives bring about not only a direct economic effect, but also ecological understanding of the improvement of human environment. The work represents aspects of the formation of economic tools of eco-economic measures, and there is calculated the economic effect. The authors of work concluded that the prospective direction is an economic approach as the basis of synergetic approach in conditions of the integration of Ukraine in the world space.